2021
DOI: 10.3390/pr9020261
|View full text |Cite
|
Sign up to set email alerts
|

Low-Viscosity Ether-Functionalized Ionic Liquids as Solvents for the Enhancement of Lignocellulosic Biomass Dissolution

Abstract: Due to the substantial usage of fossil fuels, the utilization of lignocellulosic biomass as renewable sources for fuels and chemical production has been widely explored. The dissolution of lignocellulosic biomass in proper solvents is vital prior to the extraction of its important constituents, and ionic liquids (ILs) have been found to be efficient solvents for biomass dissolution. However, the high viscosity of ILs limits the dissolution process. Therefore, with the aim to enhance the dissolution of lignocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Service quality was found to have no effect on customer satisfaction with a mobile food delivery application. These results do not correlate with the findings found Rahim et al (2021). Parastanti (2014) revealed that customers are satisfied if good service quality is provided by e-hailing food delivery during MCO.…”
Section: Resultsmentioning
confidence: 74%
“…Service quality was found to have no effect on customer satisfaction with a mobile food delivery application. These results do not correlate with the findings found Rahim et al (2021). Parastanti (2014) revealed that customers are satisfied if good service quality is provided by e-hailing food delivery during MCO.…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, on the basis of experimental density values, the molecular volume (V) at T = 298.15 K, the lattice energy (UPOT) and the standard molar entropy (Sº) at T = 298.15 K were calculated using the following equations [ 35 ]: V = M w ⁄(N· ρ ) U POT = 1981.2·[( ρ ⁄M w ) 0.33 ] + 103.8 Sº = 1246.5 (V) + 29.5 where M w is the molar mass and N is Avogadro’s constant (6.022·10 23 mol −1 ). The following parameters λ, ρ 0 , V, Sº, U POT , calculated from the equations listed above are in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the glucan fraction in the DES-G pretreated EFB increased when the ratio was increased to 1:10, with a glucan fraction of 48.9% ± 0.8%, but this fraction was subsequently reduced as the ratio was increased to 1 to 20, which was likely caused by the amorphous region dissolution in the solvent. Rahim et al (2021) reported that the low viscosity of 1-(2-methoxyethyl)-3methylimidazolium chloride (MOE-MImCl) is a primary factor in improving the dissolution of bamboo in ILs, since it boosts the mass transfer of the solute, thus leading to a higher percentage of biomass dissolution. Thus, the DES viscosity can influence the biomass to solvent ratio during the pretreatment process.…”
Section: Effects Of the Empty Fruit Bunch (Efb) To Solvent Ratio Empty Fruit Bunch (Efb) Dissolution And Chemical Composition Of Deep Eutmentioning
confidence: 99%